Immune memory to hepatitis B virus in 4-to-9-year old children vaccinated in infancy with four doses of hexavalent DTPa-HBV-IPV/Hib vaccine - Zinke, Michael; Kappes, Rudolf; Kindler, Klaus; Paulus Koschik, Anke; Goering, Uwe; Disselhoff, Johann; Soemantri, Peter; Grunert, Detlef; Laakmann, Karl Heinz; Gunasekaran, Ramakrishnan; Gartner, Britta; Marie Jacquet, Jeanne (Human vaccines, 2009)
The combined hexavalent diphtheria-tetanus-acellular pertussis-hepatitis B-inactivated polio Haemophilus influenzae type b (DTPa-HBV-IPV/Hib) vaccine produces similar hepatitis B responses as the HBV monovalent vaccine. Booster vaccination of immunocompetent individuals primed against hepatitis B in infancy is currently not recommended. We investigated persisting immunity to hepatitis B in 4-6 (Study A; 106745) and 7-9 (Study B; 106744) year-old children primed in infancy and boosted in the second year of life with DTPa-HBV-IPV/Hib. Immunity was assessed by measuring persisting anti-HBs antibodies and evaluating the response to a challenge dose of HBV vaccine. At 4-6 years of age 86.0% of 186 subjects had persisting anti-HBs ≥10mIU/ml increasing to 98.4% after the challenge. At 7-9 years of age, 78.0% of 186 subjects continued to have anti-HBs antibody concentrations ≥10mIU/ml, increasing to 98.9% after the challenge. In both studies anti-HBs antibody GMC rose >80-fold. An anamnestic response to the HBV challenge was observed in 95.7% and 98.9% of subjects in Studies A and B, respectively. In both studies, 87% of 38 subjects with initially undetectable circulating anti-HBs antibodies (